Building Capacity at Asian American and Native American Pacific Islander-Serving Institutions (AANAPISI): Transforming the Educational Experiences of Asian American and Pacific Islander (AAPI) Students - Nguyen, Mike Hoa (The Journal of higher education (Columbus), 2022)
This study examines how Asian American and Native American Pacific Islander-Serving Institutions (AANAPISI) build capacity for student success. By contrasting a community college on the West Coast and a regional comprehensive university on the East Coast, new pathways are forged to recognize the critical role that federally-funded AANAPISIs play in supporting Asian American and Pacific Islander students. Implications for policy, practice, and research are also offered to advance the operations and understanding of AANAPISIs.